2020
DOI: 10.1109/access.2020.3004933
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of COVID-19 Based on Multisource Data From a Geographical Viewpoint

Abstract: In June 4, 2020, Corona Virus Disease 2019(COVID-19) cases in Wuhan were cleared, and the epidemic situation was basically controlled. Such public safety infectious disease includes influences great pressure on the national economy. At present, some countries and regions in the world are still in epidemic situation, and there is an urgent need to judge the infection situation and travel risk in the region. In a relatively fine scale down to perceive the surrounding situation, and then rational zoning decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…They enable computer applications to be extended to the fields of humanities, social sciences, and complex systems. Some other methods are listed as follows [103][104][105][106][107] :…”
Section: Many Other Methods Have Also Been Proposedmentioning
confidence: 99%
“…They enable computer applications to be extended to the fields of humanities, social sciences, and complex systems. Some other methods are listed as follows [103][104][105][106][107] :…”
Section: Many Other Methods Have Also Been Proposedmentioning
confidence: 99%
“…Based on mobile phone and confirmed patient data, Jia et al [24] developed a spatiotemporal “risk source” model to determine the geographic distribution and growth pattern of COVID-19 and quickly as well as accurately assess the related risk. Zhang et al [25] used the GeoDetector and the decision tree model to identify the main factors in low- and high-risk areas by combining multi-source data. Loske [26] explored the relationship between COVID-19 spread and transportation volume in food retail logistics by combining transport volume data and confirmed patient data.…”
Section: Related Workmentioning
confidence: 99%
“…In [40] , the authors presented a basic SEIR model to model the COVID-19 spread in India and used it to simulate and evaluate different scenarios of the spread based on the transmission rate and finally, they proposed potential future evolution of the spread and possible mitigation. Along with mathematical modelling, in [41] , the authors employed a machine learning algorithm namely, the decision tree algorithm, to study the indicators responsible for the evolution of COVID-19 pandemic using multi-sourced data. The study identified the population density as one of the most important determinants of infection spread.…”
Section: Introductionmentioning
confidence: 99%